Elementary School And Agriculture Regeneration: Looking At Elementary School Students' Perceptions Of Work In The Agricultural Sector And The Influencing Factors - Nugraha, Yogaprasta Adi; Valdiani, Dini; Nugroho, David Rizar; Abdillah, Salman (UNIVERSITAS PAKUAN, 2023)
There are various reasons for the decline in interest of young workers in the agricultural sector, especially the low regeneration of young people working in the agricultural sector. This research focuses on the work aspirations of elementary school students, especially regarding agriculture which is narrated in elementary schools and elementary school students' views on work in the agricultural sector. Elementary school plays an important role in developing initial ideas about a job. Employment aspirations in villages are strongly influenced by how basic education builds narratives about the existing jobs. This research found students who have experience in agriculture sector tend to have positive perception towards agricultural work.